Semi-analytical Approach for Prediction of Freezing Times of Regular Shaped Foods - Kumar , Sanoj (Journal of Postharvest Technology, 2016)
Food freezing is one of the most significant applications of refrigeration. In order for freezing operations to be cost-effective, it is necessary to optimally design the refrigeration equipment. This requires estimation of the freezing times of foods. Estimation of food freezing time analytically is not possible, and numerous semi analytical methods for predicting food freezing times are available. A new method has been proposed for the prediction of freezing time and the performance of these various methods is evaluated in this paper by comparing their results to experimental freezing time data obtained from the literature. The proposed method shows error ranges upto 10 %, hence may be used for estimation of food freezing time.